2010
DOI: 10.1111/j.1432-2277.2009.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric outcome analysis of sirolimus-based immunosuppression in 252 liver transplant recipients

Abstract: Summary The use of sirolimus (SRL) in orthotopic liver transplantation (OLT) has been controversial after experimental data suggested an increased risk of hepatic artery thrombosis (HAT). To assess the safety and efficacy of SRL as de novo immunosuppression in OLT recipients. Outcomes of 252 OLT patients who received SRL were compared with outcomes of 291 OLT recipients who received calcineurin inhibitor in a retrospective study. Primary outcomes of this study were: patient‐ and graft survivals, vascular, bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 73 publications
2
33
1
Order By: Relevance
“…Published experience of de novo use of sirolimus subsequent to this trial has been limited to observational and retrospective studies, which have not shown an increased risk of graft failure or HAT (15,20,31). Rates of HAT seen in the sirolimus arm in this study (8%) were much higher than those in other single-and multicenter observational studies (approx.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Published experience of de novo use of sirolimus subsequent to this trial has been limited to observational and retrospective studies, which have not shown an increased risk of graft failure or HAT (15,20,31). Rates of HAT seen in the sirolimus arm in this study (8%) were much higher than those in other single-and multicenter observational studies (approx.…”
Section: Discussioncontrasting
confidence: 47%
“…Indeed, salient features that may differentiate the favorable experience of single centers using sirolimus versus those reported in the current study may be a lower total dose of immunosuppression and/or amelioration of factors that may be associated with a thrombotic tendency (e.g. elevated hematocrit or timing of administration) (12,18,31).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The incidence of HAT related to sirolimus use varies in different reports. Molinari et al [78] reported a higher incidence of HAT in sirolimus group with CNI group but no HAT was reported in LT recipients on sirolimus in another study by Harper et al [79] . Similar results were reported by Fischer et al [80] , and they did notice no HAT following conversion of CNIs to everolimus.…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 98%
“…However, this drug has also been used off-label in liver and lung transplantation patients [24][25][26][27] . At our center, the use of everolimus in LT recipients is approved in situations such as renal dysfunction or adverse events like neurotoxicity due to CNI, development of de novo malignancies, recurrence of hepatocellular carcinoma, and the presence of predictors of a high risk of hepatocellular carcinoma recurrence in the explanted liver (satellitosis, vascular infiltration and multinodularity disease) [28,29] .…”
Section: Methodsmentioning
confidence: 99%